The Synergy Approach and Structured Repertorization - Sankaran, Rajan (Homœopathic Links, 2013)
The concept of Synergy denotes the coming together of two or more things to create an effect that is much greater than the sum of the two. In homeopathic practice, using two or more different approaches in tandem produces the best results. The utilization of traditional homeopathic tools such as materia medica and the repertory in combination with more modern homeopathic approaches such as sensation and kingdom, generate the most success in clinical practice. In tandem with Synergy, Structured Repertorization is a useful tool to aid in reconstructing a patientʼs experience in an exact manner.
Keywords: Case-taking; Synergy; Genius; System; Symptom; Anchor; Structured repertorization; Tuberculinum